2016
DOI: 10.1097/ico.0000000000000945
|View full text |Cite
|
Sign up to set email alerts
|

Positive End-Expiratory Pressure as a Risk Factor for Severe Positive Vitreous Pressure During Combined Penetrating Keratoplasty and Cataract Extraction

Abstract: During open-sky procedures, PEEP may be a risk factor for severe positive posterior vitreous pressure. Given the rising use of PEEP, surgeons should be aware and cautious of this potential complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Increased systemic venous pressure due to a variety of causes including positioning of the head below the heart, congestive heart failure, pulmonary edema, obstructive sleep apnea, chronic obstructive pulmonary disease, 20 Valsalva https://doi.org/10.2147/OPTH.S382502…”
Section: Patient-related Risk Factorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Increased systemic venous pressure due to a variety of causes including positioning of the head below the heart, congestive heart failure, pulmonary edema, obstructive sleep apnea, chronic obstructive pulmonary disease, 20 Valsalva https://doi.org/10.2147/OPTH.S382502…”
Section: Patient-related Risk Factorsmentioning
confidence: 99%
“… 16 Pillar et al reported 2 cases of increased PVP caused by the use of positive end-expiratory pressure (PEEP) during general anesthesia. 20 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other risk factors associated with the open-sky state and the patient's health status, such as previous ocular surgery, ocular trauma, internal diseases (arterial hypertension, coronary heart disease, diabetes, atherosclerosis, etc. ), and the choice of general anaesthesia, may also constitute contraindications for IOL implantation during a single surgery [ 5 – 9 ]. However, secondary IOL implantation is a challenging surgical procedure and demands suitable ocular conditions.…”
Section: Introductionmentioning
confidence: 99%